THE EFFECT OF USING PICTURE DESCRIBING AND STORYTELLING ON YOUNG LEARNERS' SPEAKING ACHIEVEMENT - Gracia Precilya Pratami (Widya Mandala Surabaya Catholic University, 2020)
This study concerns the effect of using Picture Describing and Storytelling to the 5th grade students' speaking achievement. This study was accomplished in the second year of a private Primary School in Kupang which consisted of 48 students as the participants. The writer used quasi-experimental research using nonrandomized pre-test and post-test group as her design. The writer found out that the gain scores’ mean of pre-test and post-test in the experimental group was 6 and the gain scores’ mean of pre-test and post-test in the control group was 3. With the level of significance at 5%, the writer found out that the t observation (to) of the experimental group and the control group was 2.476. Since to (2.476) is greater than t-table (2.015), so Ho is rejected and Ha is accepted. It means that there is a significant difference between the speaking achievements of students who were taught using Picture Describing and students who were taught using Storytelling.